J & p transformer book - Heathcote, Martin (Newnes, 2007)
The J & P Transformer Book has been in print for 80 years, and is renowned internationally as the definitive reference work covering the design, construction, installation, monitoring and maintenance of power transformers in electricity generation and distribution, electricity substations, and industrial applications. The broad scope of the Transformer Book and its practical focus makes it ideal reading for graduate engineers embarking on a design career, students of electrical engineering, and a broader audience in the power engineering and transformer manufacturing sectors. However, it is not a text to read once and consign to the shelf, but rather a hard-working working reference for the seasoned professional as well as the novice. The thirteenth edition includes new sections and updates throughout, referencing the latest International (IEC) and European standards. New material includes coverage of recent developments in amorphous steels, and expanded coverage of the competitive area of small distribution transformers. *The definitive reference for all involved in designing, installing, monitoring and maintaining high-voltage systems using power transformers (electricity generation and distribution sector; large-scale industrial applications) *The classic reference work on power transformers and their applications: first published in 1925, now brought fully up to date in this thirteenth edition *A truly practical engineering approach to design, monitoring and maintenance of power transformers in electricity generation, substations, and industrial applications.
Keywords: Electric transformers.; elektronické knihy; electronic books